2017
DOI: 10.1177/2056305117707187
|View full text |Cite
|
Sign up to set email alerts
|

Mothering on Facebook: Exploring the Privacy/Openness Paradox

Abstract: To post or not to post photographs of children? Is it worth commenting on potentially controversial topics such as vaccinations and breastfeeding in a public forum or even a private group? Facebook offers mothers of young children a range of affordances that were unimaginable in a pre–social networking site (SNS) era, but at the same time presents a new set of dilemmas surrounding parenting in the digital domain. The SNS activity of parents brings the lives of children into online spaces in a way that builds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 32 publications
5
67
0
7
Order By: Relevance
“…Social media provided them with connections to others around the world; but also, crucially, were able to act as forums for very localised knowledges and to facilitate face-to-face friendships (studies by Johnson [28] and Chalken [18] revealed similar findings). There was a reciprocal relationship between in-person interactions and online media.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Social media provided them with connections to others around the world; but also, crucially, were able to act as forums for very localised knowledges and to facilitate face-to-face friendships (studies by Johnson [28] and Chalken [18] revealed similar findings). There was a reciprocal relationship between in-person interactions and online media.…”
Section: Discussionsupporting
confidence: 57%
“…The discussion here presented contributes to previous work in this area in several ways: by focusing on the experiences of Australian women (a group that has received little attention thus far); by addressing the full panoply of digital media that are now available to women for both pregnancy and parenting rather than focusing on one media type alone, as most other studies have done; and by considering the complexities of the intersections between information, emotional support, intimacy, personal data generation, sharing and privacy as they are conducted and experienced on the digital media used by women during these life stages. The handful of studies published thus far on the Australian context have found that women are actively using apps and social media for pregnancy and parenting [18,[27][28][29][30]. However, little research has yet investigated the details of how Australian women take up these media in relation to each other, and across their experiences of pregnancy and into the early parenting period.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small number of articles have begun to investigate the ways in which digital technologies become interwoven in everyday mothering practice (e.g. Blum‐Ross & Livingstone, ; Chalklen & Anderson, ; Frizzo‐Barker & Chow‐White, ; Johnson, , ; Moravec, ). For example, specific apps act as tools to embody “good” mothering ideals (such as using apps that allow child development tracking) as well as providing a means to delegate some responsibilities (vaccine timers, notifications, scheduling).…”
Section: Mothering In a Digital Agementioning
confidence: 99%